Analisis Pengaruh Berat Roller Standard Dan Racing Pada Sistem Cvt Terhadap Rpm Sepeda Motor Honda Beat Pgm-Fi Tahun 2015 - Amin Nur Akhmadi; Mukhamad Khumaidi Usman (Rekayasa Material, Manufaktur dan Energi, 2021)
Currently, automotive products, especially two wheels (motorbikes), are equipped with an automatic transmission system. The type of automatic transmission used is CVT (Continously Variable Transmission). A roller is a material that is composed of Teflon as the outer surface and copper or aluminum as the inner layer. The function of the roller is to press the inner wall of the primary pulley during high rotation. RPM (Revolution Per Minute) is the number of rounds done in one minute. The purpose of this study is to determine the results of RPM on the effect of roller use and to determine the comparison of the effect of using a weight variation of a 13 gram (standard) roller and a 10 gram (racing) roller on the RPM of a 2015 Honda Beat FI motorcycle. 4 steps. The research method used is an experimental method, namely by starting the engine and holding the throttle at 1400-1500 RPM after stabilizing then the throttle is rotated spontaneously up to 9000-9500 RPM. The results of this study can be concluded that the 10 gram roller on the primary and secondary pulleys only get good acceleration and RPM at low rotation speeds. Whereas at high rotational speed the RPM acceleration is less than optimal.